Approaches in Drinking Water Provision in Developing Countries: An Investigation of Water Safety Plans and Ceramic Water Filters - String, Gabrielle. (2017)
Abstract: Primarily, two interventions are advocated to address water safety concerns and work towards the Sustainable Development Goal (SDG) of populations drinking water from safely managed sources by 2030: Water Safety Plans (WSPs) and household water treatment (HWT). This dissertation investigated technologies associated with safe water provision at two scales: community (i.e. WSPs) and household (i.e. ceramic water filters). First, a systematic review of WSPs was conducted to understand the current evidence and knowledge gaps in these implementations to better inform key stakeholders of research needs. Overall, 53 documents met inclusion criteria; evidence in support of financial and operational outcomes from WSP implementations was prevalent, but evidence on institutional and policy outcomes were lacking. Second, a multi-country evaluation of rural, community-managed WSP implementations was conducted using a mixed methods protocol to evaluate how the WSP process was translated into these contexts and the functionality of the resulting implementations. In total, 817 household surveys, 1,113 water quality samples, and 256 focus groups and key informant interviews were completed. Overall, we found: 1) incomplete WSP implementations; 2) no documented microbiological water quality improvements in WSP-communities; and, 3) small water supply operations improvements. These results highlight the need for complete WSP implementation with sufficient support, and question whether WSPs are the appropriate strategy for community-managed water systems. Third, X-ray micro-computed tomography was used on ceramic water filters to characterize the pore network morphology of engineered pathways from four different filters. Results indicate 1) similarities in porosity (25-36%) and pore size distributions (mean pore radius 7.8-14.3 um) between filters manufactured under different parameters; 2) preferential alignment of pores normal to the direction of flow for rice husk pore-formers; and, 3) varying tortuosity factors (13.7-38.9) in a filter made with rice husk pore-formers as compared to tortuosity factors (3.8-5.2) in a filter made with sawdust when both filters have uniform porosity in the through-thickness direction. To assure delivery of safe drinking water, a strategy integrating both intervention methods, WSP and HWT, would address safe water supply concerns across a broad spectrum. Further development and adaptation of these technologies is critical to achieving the SDGs.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Mechanical Engineering.; Advisors: Douglas Matson, and Daniele Lantagne.; Committee: Iryna Zenyuk, Jeff Gostick, and Roger Singleton.; Keyword: Environmental engineering.